Pemetaan Sebaran Penyakit Demam Berdarah Dengue Di Kota Lhokseumawe Tahun 2022-2023 - Roffa, Muhammad Abraar Roffa (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Dengue Hemorrhagic Fever (DHF) has become a significant health issue that needs to be addressed in the healthcare sector in Indonesia. The number of DHF cases in the city of Lhokseumawe has witnessed an increase from 2022 to 2023. The objective of this research is to identify the areas of DHF prevalence in Lhokseumawe, then map these areas based on the gender and age range of the patients, presented in the form of a map. The research methodology employed is descriptive research using secondary data, including clinical information and administrative data of DHF patients in Lhokseumawe, as well as demographic data of Lhokseumawe. Data processing is conducted using the QGIS 3.30 application, utilizing the equal interval formula automatically provided by the application. The research indicate the presence of 41 DHF cases in Lhokseumawe spread across all sub-districts. Muara Dua Sub-district recorded the highest number of 20 cases, representing 48% of the total cases. In contrast, Blang Mangat Sub-district reported the lowest number of cases, constituting 2% of the total cases. Based on the classification of gender and age, DHF cases in Lhokseumawe tend to occur more frequently in males, with a male presentation of 51.2%, and females with 48.8% of the total number of cases. Age classification includes three categories: 0-14 years, 15-44 years, and >44 years, with the prevalence of cases in the age group 0–14 years at 39.0%, 15–44 years at 43.9%, and 44 years or older at 17.1% of the total number of cases."